2016
DOI: 10.1002/ijc.30141
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B2 intake and colorectal cancer risk; results from the Nurses' Health Study and the Health Professionals Follow‐Up Study cohort

Abstract: Vitamin B2 serves as a cofactor to enhance one-carbon metabolism, maintain mucous membranes, and has been implicated in lowering colorectal cancer (CRC) risk. However, few prospective studies have examined the association between vitamin B2 intake and CRC. In this study, we estimated the associations between vitamin B2 intake and CRC risk using the Nurses’ Health Study (NHS) and the Health Professionals Follow-Up Study (HPFS) cohorts. Vitamin B2 intake was measured by a validated food frequency questionnaire e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 44 publications
(148 reference statements)
2
17
0
Order By: Relevance
“…Stratified analysis by alcohol consumption suggested that there was no indication of effect modification between B vitamins and methionine and colorectal cancer by alcohol consumption. Consistent with our results, some previous studies found no significant interaction in the associations between folate (16,52) , vitamin B 2 (46,47) , vitamin B 6 (56,57) , vitamin B 12 (47,56) and methionine (47,52) and colorectal cancer risk modified by alcohol consumption. However, the National Institutes of Health-American Association of Retired Persons Diet and Health Study showed total folate intake-associated colorectal cancer risk reductions among men and women drinkers (both >15 and ≤15 g/d) but not non-drinkers (13) .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Stratified analysis by alcohol consumption suggested that there was no indication of effect modification between B vitamins and methionine and colorectal cancer by alcohol consumption. Consistent with our results, some previous studies found no significant interaction in the associations between folate (16,52) , vitamin B 2 (46,47) , vitamin B 6 (56,57) , vitamin B 12 (47,56) and methionine (47,52) and colorectal cancer risk modified by alcohol consumption. However, the National Institutes of Health-American Association of Retired Persons Diet and Health Study showed total folate intake-associated colorectal cancer risk reductions among men and women drinkers (both >15 and ≤15 g/d) but not non-drinkers (13) .…”
Section: Discussionsupporting
confidence: 92%
“…The present study showed that intakes of folate, vitamin B 2 and vitamin B 6 were inversely associated with colorectal cancer both in men and women, whereas vitamin B 12 and methionine intakes were found to be related to decreased risk of colorectal cancer only among women. These sex differences have been reported in previous studies; however, the results were inconclusive (13,21,28,46,52) . Consistent with our results, one cohort study conducted in the Netherlands found that methionine was associated with a decreased risk of rectal cancer among women (52) , but a 2013 meta-analysis of eight prospective studies indicated that a significant inverse association was observed between dietary methionine intake and colorectal cancer risk only in men but not in women (28) .…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Regarding the risk of colorectal cancer , after adjustments for potential confounders, no association with riboflavin intake was found in most cohorts (de Vogel et al., ; Kabat et al., ; Shrubsole et al., ; Key et al., ; Yoon et al., ). In one cohort (Zschabitz et al., ) included in the systematic review below, no association was shown with riboflavin intake from food or from supplement, but a significantly increased risk was observed in the highest quartile of total riboflavin intake (food and supplements) compared to the lowest one.…”
Section: Criteria (Endpoints) On Which To Base Dietary Reference Valuesmentioning
confidence: 99%
“…To our knowledge, this is the first report on the potential interaction between serum B‐vitamin alterations and their prognostic values in DLBCL. Previous studies indicated no significant impact of daily intake of vitamin B2 on cancer risks, such as urothelial cell carcinoma, 40 colorectal cancer 41 and NHL 42‐44 . Daily intake of B vitamins, instead of serum B vitamins, were collected in these articles, which could lead to different conclusions.…”
Section: Discussionmentioning
confidence: 96%